Metodologi A. Mukti Ali Dalam Penafsiran Alqurān: Analisis Terhadap Kitab Tafsir Alqurān di Nusantara - Abdurrahim Bin Safran (Universitas Islam Negeri Sumatera Utara, 2018)
The aim of this study is to find the method of A. Mukti Ali Interpretation towards Alquran, also the analysis of Alquran exegesis in Nusantara. Alquran and the exegesis of A. Mukti Ali is one of exegesis book in Indonesia which officially by government in decree No. 26 tahun 1967 as a main reference in understanding Alquran. The method used in this study is library research. The finding shows that the importance of deeply learning Alquran from many perspective. In addition to studying Alquran relating to shahabat era and relevant to nowadays life.